Variações sazonais na ultra-estrutura do ducto deferente de codorna doméstica (Coturnix coturnix) - Viegas, Kátia Aparecida da Silva; Orsi, Antonio Marcos [UNESP]; Domeniconi, Raquel Fantin [UNESP]; Matheus, Selma Maria Michelin [UNESP]; Schimming, Bruno César [UNESP] (My University, 2011)
The vas deferens (VD) of domestic quail showed seasonal variability on the fine structure of the lining tubular epithelium during the four seasons along the year, whose features were marked more relevant in the autumn and spring which respectively corresponded to the quiescent and active phases of the annual testis cycle (“cycle”) in this species. During the fall quiescence had been verified tubular reduction of the VD caliber and luminal dimension followed by degenerative features of the principal epithelial cells and lack of luminal content of spermatozoa. Counter wise in the spring active phase of the "cycle” great dimension of the VD caliber and luminal dimension were observed and the luminal content was plenum of material represented prior by spermatozoa. Similar features occurred on the VD fine structure in the summer and winter according to our results. Fine structural features of the VD lining epithelium in the spring showed variability of cytoplasm organelle mainly related to active processes of endocytosis and protein synthesis, although more lysosomal activity was seen on the apical cytoplasm of principal epithelial cells in the recrudescent phase of winter. Moreover, it was verified a relative scarcity of cytoplasm organelle followed by presence of dark epithelial cells in the regressive phase of summer.

O ducto deferente (DD) de codorna doméstica mostrou variações sazonais na ultra-estrutura do epitélio de revestimento tubular nas quatro estações do ano, sendo, contudo, mais marcantes no outono, que corresponde à fase quiescente, e na primavera, que é a fase ativa do ciclo testicular anual. Durante a quiescência outonal ocorreram redução do calibre e da luz tubular do DD e características de degeneração celular das células principais (P) do epitélio do DD. A fase ativa primaveril mostrou o calibre tubular e a dimensão luminal maiores do DD, ocorrendo grande estoque de material intra-luminal formado principalmente por espermatozoides. A ultra-estrutura do epitélio de revestimento do DD na fase ativa primaveril mostrou variabilidade das organelas citoplasmáticas relacionadas, principalmente, aos processos de síntese proteica e de endocitose. Contudo, foi observada uma maior quantidade de lisossomos no citoplasma apical de células P do DD na fase recrudescente do inverno, assim como uma escassez relativa de organelas citoplasmáticas e presença de células escuras na fase regressiva do verão.
Seasonal variability on the ultrastructure of the vas deferens of domestic quail (Coturnix coturnix)
Keywords: Vas deferens; Ultrastructure; Quail; Codorna; Epitélio de revestimento; Ultra-estrutura